2019
DOI: 10.1103/physreva.100.053829
|View full text |Cite
|
Sign up to set email alerts
|

Temporally multimode four-photon Hong-Ou-Mandel interference

Abstract: The two-photon Hong-Ou-Mandel (HOM) interference is a pure quantum effect which indicates the degree of indistinguishability of photons. The four-photon HOM interference exhibits richer dynamics in comparison to the two-photon interference and simultaneously is more sensitive to the input photon states. We demonstrate theoretically and experimentally an explicit dependency of the four-photon interference to the number of temporal modes, created in the process of parametric down-conversion. Moreover, we exploit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…However, the degenerate and non-degenerate squeezed states in Eqs. ( 4) and ( 6) are not entirely equivalent for quantum interference experiments, when the Schmidt modes involve the degrees of freedom not affected by a multiport (e.g., the spectral shape of photons) [39,[48][49][50][51]. In Eqs.…”
Section: Squeezed States In the First-order Quantization Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the degenerate and non-degenerate squeezed states in Eqs. ( 4) and ( 6) are not entirely equivalent for quantum interference experiments, when the Schmidt modes involve the degrees of freedom not affected by a multiport (e.g., the spectral shape of photons) [39,[48][49][50][51]. In Eqs.…”
Section: Squeezed States In the First-order Quantization Representationmentioning
confidence: 99%
“…Squeezed states are inevitably multimode, thus one would like to know if their multi-mode structure induces partial distinguishability. Though some experiments have shown that the multi-mode structure is shaping the interference with the squeezed states [39], there were no clue of how one could approach such a problem.…”
Section: Introductionmentioning
confidence: 99%
“…e −H(ta,t b ,tc,t d ,δa,δ b ,δc,δ d ) }, (15) where, H is defined as: For the time width δ d = 0.1 , the time delay 3 between two input pulses as τ c changes gives two peaks. This is because the time width is short enough to seperate the two peaks.…”
Section: Time-dependent Hong-ou-mandel Interferencementioning
confidence: 99%
“…As an example, it has been demonstrated that the possibility of controlling the number of spectral modes, and therefore the amount of spectral/temporal correlations between signal and idler photons, can determine the behaviour of the quantum interference pattern in the four-photon Hong-Ou-Mandel scenarios [27].…”
Section: Introductionmentioning
confidence: 99%